N06 Patient perspectives on the role of the IBD nurse and telemedicine during COVID-19 pandemic: results from a Belgian tertiary IBD unit. (27th May 2021) - Dewitte, G; Geldof, J; Truyens, M; Lobaton, T
Abstract: Background: Many inflammatory bowel disease (IBD) patients experienced additional stress due to the COVID-19 pandemic. Concerns for COVID-19 disease increased the risk of immunomodulatory or biologic treatment discontinuation. Furthermore, lockdown threatened the continuity of chronic care delivery. To guarantee the continuity of care our IBD unit rapidly adapted and developed new ways of remote communication. This included telephonic clinics and telephonic pre-admission screening before every appointment at the dayclinic. In this process the IBD nurse played a pivotal role. The aim was to assess patients' concerns during the first COVID-19 wave and their acceptance of telemedicine. Methods: A cross-sectional study was performed using an anonymous electronic questionnaire (REDCap®) to assess IBD patients' satisfaction regarding care delivery at the IBD unit of the Ghent University Hospital during the first COVID-19 wave. Results: A total of 274 patients participated. Mean age was 47.5 years (SD ± 15.4). According to patients' answers, 57.2% had Crohn's disease, 34.5% ulcerative colitis and 8.3% reported 'other'. During the first wave, 43.6% of patients contacted their IBD nurse; usually questions regarding medication (20.6%), appointments (18.4%) or SARS-CoV2 infection risk (6%). For the majority of patients (96.5%) these contacts were sufficient. In person follow-up consultation was scheduled for 178 patients. From those, 31 considered cancelling their consultation due to the pandemic and 18 effectively cancelled (Fig 1). Half of the population (51.6%) received intravenous therapy at the day clinic. Telephonic pre-admission screening the day before was done for all patients and well received in most of them (98.5%). During the first wave, endoscopy was planned in 31.5% of the responding patients. A minority (11.1%) postponed or cancelled endoscopic appointments. From those, 55.6% reported that the main reason was fear of the coronavirus. Ninety-four (39.2%) of responders had a telephonic consultation during the first wave. Different aspects regarding satisfaction and acceptance of telemedicine were also assessed (Fig 2–3). For further follow-up, 60.2% preferred balanced combination of telephonic and face-to-face consultations. Conclusion: Remote ways of care delivery were generally well received during the first wave of the pandemic. Only a minority of patients cancelled appointments without discussion with the medical team. The most frequent patient concerns were about medications and appointments. The challenges in continuity of care during the pandemic created a window for new ways of care delivery in the future.